Characterization and comparison of copper coatings developed by low pressure cold spraying and laser cladding techniques. (2019) - Singh, Surinder; Singh, Parminder; Singh, Harpreet; Buddu, Ramesh Kumar
Abstract: Copper coatings of 3-mm thickness were developed by both cold spraying and laser cladding techniques on SS316 steel. The developed coatings were then characterized with various techniques to evaluate metallurgical and mechanical properties. Tensile strength (170 MPa) of the cold sprayed coating was found to be comparable with that of the laser cladded coating, whereas %age elongation of laser cladding (11%) was almost double (6%) of that for the cold sprayed coating. Porosity was found to be low in the cold sprayed coating as compared to that in the laser cladding, which indicates that the former technique could give a denser coating. This difference in porosity led to relatively higher electrical and thermal conductivity in the cold sprayed coating as compared to the laser cladding. X-ray diffraction and electron disperse spectroscopy analyses revealed the absence of oxide formation in the cold sprayed coating, however oxides were seen in the laser cladding. Also, a large heat affected zone (HAZ) was detected in the laser cladding, whereas no HAZ was observed in the cold sprayed coating. Hardening was observed along the interface and HAZ of the cladded steel, which may be attributed to the diffusion of carbon from the substrate